ANALISIS SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI PADA PROYEK PRESERVASI JALAN BTS. ACEH TENGAH/NAGAN RAYA–LHOK SEUMOT–JEURAM - Firdausi Nuzula; Sofyan M Saleh; Yusria Darma (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2023)
Based on the number of work accidents in the construction industry sector that get a relatively high percentage, it is necessary to identify the application of SMKK through the research "Analysis of the Occupational Safety and Health Management System (SMKK) there is a Construction Project (Case Study on the Bts. Aceh Tengah / Nagan Raya Road Preservation Project - Lhok Seumot - Jeuram)" . Therefore, this study aims to find out the extent of the application of SMKK to road construction work and find out the perception of construction actors in the work towards the application of SMKK. This research was conducted by distributing SMKK questionnaires to correspondents consisting of owners, supervising consultants, project work implementers and sub-implementers of work. SMKK questionnaire sampling uses a simple random sampling technique or a simple random sample to be used as a sample. The preparation of the SMKK questionnaire was first carried out a validity test. The Princple Component Analysis (PCA) factor analysis method is used to explore the relationship between factors and smkk application indicators using SPSS Statistics software. The results of the rotation of factors and the variance of factors formed that affect or that are of concern to respondents to the application of SMKK at the job location are (1) K3 audit and evaluation factors of 30.52%; (2) K3 communication and training factor of 7.73%; (3) K3 discipline and communication factor of 6.99%; (4) K3 communication, inspection and investigation factors of 6.33%; (5) communication and K3 policy factors of 5.61%; (6) procedural and coordination factors of 5.10%; (7) responsibility and commitment factors of 4.67%; (8) the K3 responsibility and policy factor of 4.01%; and (9) the K3 evaluation factor of 3.68%. The results of the factor analysis show that respondents or construction workers tend to pay more attention to the audit and evaluation of K3 as the application of SMKK at the location of the Bts. Aceh Tengah / Nagan Raya Lhok Seumot-Jeuram road preservation project.